Strategi Supervisi Akademik Integratif Kepala Madrasah untuk Pengembangan Profesionalisme Guru - Moh Zahiq; Ananda Wira Kusuma (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2025)
This article aims to analyse the Integrative Academic Supervision Strategy of Madrasah Principals for Teacher Professionalism Development as an effort to improve teacher professionalism. This study uses a qualitative approach with a descriptive research type. Data were collected through in-depth interviews, participatory observation, and documentation study, then analysed through the stages of data reduction, data presentation, and interactive conclusion drawing. The results showed that the madrasah principal successfully integrated the three functions synergistically. The managerial function was manifested in systematic and participatory supervision planning. The pedagogical function was evident in teacher development through reflective dialogue and professional training. Meanwhile, the evaluative function was applied through continuous assessment accompanied by constructive follow-up. The integration of these three functions not only improved teachers' pedagogical competence but also fostered a collaborative and reflective culture in the madrasah environment. This article contributes to the development of Islamic education management studies by strengthening the concept of integrative academic supervision that positions the madrasah principal as an instructional leader and agent of change in improving the quality of education.